The influence of polymer scaffolds on cellular behaviour of bone marrow derived human mesenchymal stem cells - Wang, Weiwei; Bieback, Karen (Clinical hemorheology and microcirculation, 2012)
Mesenchymal stem cells (MSCs) are multipotent stem cells that can differentiate into a variety of cell types. Therefore, they are widely explored in regenerative medicine. The interaction of MSCs with biomaterials is of great importance for cell prol